Direct Preparation of Indole Hemiaminals through Organocatalytic Nucleophilic Addition of Indole to Aldehydes - Zhang, Nan; Li, Yige; Chen, Zhili; Qin, Wenling (Synthesis, 2018)
Hemiaminals are common in natural products as well as bioactive compounds. Hemiaminals with an indole moiety are particularly attractive due to the significant bioactivity of indoles. Herein, we reported an efficient organocatalyzed indole N-1 nucleophilic addition of α-oxoaldehydes to deliver various indole hemiaminals in good yields (up to 92%) and excellent regioselectivities with DABCO or triethylamine as the catalyst. The method is characterized by mild reaction conditions, widely available reagents, and general substrate scope, and it is also applicable to late-stage transformations without affecting the hemiaminal group. In addition, we carried out this reaction in an enantioselective fashion in good yields and high ee values with two general substrates.
Keywords: organocatalysis; indole; hemiaminals; nucleophilic addition